Validation of scenario-based business requirements with Coloured Petri Nets - Ribeiro, Óscar R. (2009)
A scenario can be used to describe a possible instantiation of a given business use case and can be expressed for example as a list of steps written in natural language, or by an interaction diagram. This paper discusses how a collection of scenarios, all expressed as UML2 sequence diagrams, can be described for validation purposes by a single model, written in the Coloured Petri Nets (CPN) modelling language. Due to the support for parallelism given by the CPN language, the obtained CPN model can: (1) simultaneously execute several scenarios; and (2) elegantly represent the parallel activities inside a scenario. This two-level parallelism is crucial during validation, since it allows one to detect problems that are only evident when several scenarios are in simultaneous execution and may affect each other. We exemplify our approach in a system that has a rich set of interactions with its users.